WEAPONRY OF SOCIETIES OF THE NORTHERN PONTIC CULTURE CIRCLE: 5000-700 BC - Klochko, Viktor I. (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2001)
Viktor I. Klochko's research derives its inspiration from the accomplishments of Scythology and constitutes an attempt to apply its achievements to early agrarian societies from the period before the Iron Age. The work both summarises and concludes a series of earlier publications by the author, which presented selected issues connected with the problem and appeared in earlier volumes of "Baltic -Pontic Studies" (cf. vols. 1, 2, 3, 6). The involvement of the Editorial Board in promoting the results of Viktor Klochko's research also stems from a deep conviction that there is a pressing need to encourage converging research programmes in other research centres of the physiographic and cultural border zone between the East and the West.